2022
DOI: 10.1182/blood.2021012386
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and phenotypic attributes of splenic marginal zone lymphoma

Abstract: Splenic marginal zone B-cell lymphoma (SMZL) is a heterogeneous clinico-biological entity. The clinical course is variable, multiple genes are mutated with no unifying mechanism, and essential regulatory pathways and surrounding microenvironments are diverse. We sought to clarify the heterogeneity of SMZL by resolving different subgroups and their underlying genomic abnormalities, pathway signatures, and microenvironment compositions to uncover biomarkers and therapeutic vulnerabilities. We studied 303 SMZL sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 60 publications
2
47
0
Order By: Relevance
“…WES studies of splenic marginal zone lymphoma (SMZL) [36][37][38][39][40][41] have found frequent mutations in TP53, KLF2, KMT2D, MYD88, NOTCH2, and TNFAIP3, among others, in addition to the known cytogenetic aberrations of chromosomes 7 (deletion 7q) and chromosome 3 (trisomy 3 or gain of 3q). The recent large genetic characterization study of SMZL by the International Extranodal Lymphoma Study Group (IELSG; 303 spleen samples), confirmed previous results and separated the cases into four genetic subgroups based on the involved gene modules/pathways, termed NNK (involving NF-κB, NOTCH, and KLF2), DMT (involving DNA damage response, MAPK, and TLR), CBS (involving cytokine, BcR signaling, and spliceosome), and PA (involving PI3K-AKT), of which NNK and DMT include 90% of all studied cases [42].…”
Section: Diagnostic Markerssupporting
confidence: 83%
“…WES studies of splenic marginal zone lymphoma (SMZL) [36][37][38][39][40][41] have found frequent mutations in TP53, KLF2, KMT2D, MYD88, NOTCH2, and TNFAIP3, among others, in addition to the known cytogenetic aberrations of chromosomes 7 (deletion 7q) and chromosome 3 (trisomy 3 or gain of 3q). The recent large genetic characterization study of SMZL by the International Extranodal Lymphoma Study Group (IELSG; 303 spleen samples), confirmed previous results and separated the cases into four genetic subgroups based on the involved gene modules/pathways, termed NNK (involving NF-κB, NOTCH, and KLF2), DMT (involving DNA damage response, MAPK, and TLR), CBS (involving cytokine, BcR signaling, and spliceosome), and PA (involving PI3K-AKT), of which NNK and DMT include 90% of all studied cases [42].…”
Section: Diagnostic Markerssupporting
confidence: 83%
“…Our findings are in line with the notion that secreted factors can give resistance to PI3K inhibitors, 35 , 36 and with the background of the cell line we have used, representative of the recently described NNK splenic MZL subgroup, driven by mutations in genes involved in NF-κB/NOTCH/ KLF2 . 37 IL-6 can protect cancer cells from apoptosis and DNA damage induced by drugs and can decrease sensitivity to tyrosine kinase inhibitors by activating different signaling pathways, such as the JAK-STAT, AKT-mTOR and NF-κB signaling pathways. 38 Release of IL-6 mediates resistance to the BTK inhibitor ibrutinib in Waldenström macroglobulinemia.…”
Section: Discussionmentioning
confidence: 99%
“…The detected genetic polymorphism in the KMT2C gene might have had a certain impact on the observed overexpression of H3K27m3, as KMT2C is at least one of the most important regulators of histone H3K4 methylation [ 29 ]. Bearing in mind the later-on diagnosed SDRPL, the two NOTCH2 VUS with VAF of 7% might have reflected an otherwise non-perceptible infiltration of the respective lymph node, as NOTCH2 mutations are among the most common genetic alterations in the closely related splenic MZL [ 30 ], although the exact identified variants have not been yet described.…”
Section: Discussionmentioning
confidence: 99%